The cuban heiress ebook - Cleeton, Chanel (2023)
An NPR Books We Love selection for 2023 "An unforgettable read that should be at the top of every TBR list."—NPR In 1934, a luxury cruise becomes a fight for survival as two women’s pasts collide on a round-trip voyage from New York to Havana in New York Times bestselling author Chanel Cleeton's page-turning new novel inspired by the true story of the SS Morro Castle . New York heiress Catherine Dohan seemingly has it all. There’s only one problem. It’s a lie. As soon as the Morro Castle leaves port, Catherine’s past returns with a vengeance and threatens her life. Joining forces with a charismatic jewel thief, Catherine must discover who wants her dead—and why. Elena Palacio is a dead woman. Or so everyone thinks. After a devastating betrayal left her penniless and on the run, Elena’s journey on the Morro Castle is her last hope. Steeped in secrecy and a burning desire for revenge, her return to Havana is a chance to right the wrong that has been done to her—and her prey is on the ship. As danger swirls aboard the Morro Castle and their fates intertwine, Elena and Catherine must risk everything to see justice served once and for all.